Early life stress and macaque amygdala hypertrophy: preliminary evidence for a role for the serotonin transporter gene - Coplan, Jeremy D.; Fathy, Hassan M.; Jackowski, Andrea P.; Tang, Cheuk Y.; Perera, Tarique D.; Mathew, Sanjay J.; Martinez, Jose; Abdallah, Chadi G.; Dwork, Andrew J.; Pantol, Gustavo; Carpenter, David; Gorman, Jack M.; et al. (Frontiers in Behavioral Neuroscience, 2014)
Background: Children exposed to early life stress (ELS) exhibit enlarged amygdala volume in comparison to controls. The primary goal of this study was to examine amygdala volumes in bonnet macaques subjected to maternal variable foraging demand (VFD) rearing, a well-established model of ELS. Preliminary analyses examined the interaction of ELS and the serotonin transporter gene on amygdala volume. Secondary analyses were conducted to examine the association between amygdala volume and other stress-related variables previously found to distinguish VFD and non-VFD reared animals. Methods: Twelve VFD-reared and nine normally reared monkeys completed MRI scans on a 3T system (mean age = 5.2 years). Results: Left amygdala volume was larger in VFD vs. control macaques. Larger amygdala volume was associated with: “high” cerebrospinal fluid concentrations of corticotropin releasing-factor (CRF) determined when the animals were in adolescence (mean age = 2.7 years); reduced fractional anisotropy (FA) of the anterior limb of the internal capsule (ALIC) during young adulthood (mean age = 5.2 years) and timid anxiety-like responses to an intruder during full adulthood (mean age = 8.4 years). Right amygdala volume varied inversely with left hippocampal neurogenesis assessed in late adulthood (mean age = 8.7 years). Exploratory analyses also showed a gene-by-environment effect, with VFD-reared macaques with a single short allele of the serotonin transporter gene exhibiting larger amygdala volume compared to VFD-reared subjects with only the long allele and normally reared controls. Conclusion: These data suggest that the left amygdala exhibits hypertrophy after ELS, particularly in association with the serotonin transporter gene, and that amygdala volume variation occurs in concert with other key stress-related behavioral and neurobiological parameters observed across the lifecycle. Future research is required to understand the mechanisms underlying these diverse and persistent changes associated with ELS and amygdala volume.